Law Enforcement Model for the Execution of Court Decisions on Civil Servant Fathers' Child Support Obligations After Divorce in the Bengkulu High Religious Court Area - Maman Abdur Rahman; Idzam Fautanu; Hasan Bisri; Aden Rosadi; Ahmad Hasan Ridwan (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2024)
Law enforcement of child support obligations of fathers as Civil Servants (PNS) after divorce often encounters obstacles, such as non-compliance in implementing Religious Court rulings. This study focuses on the Bengkulu High Religious Court (Pengadilan Tinggi Agama, PTA), which has implemented an execution system to ensure the financial rights of women and children after divorce.The primary objective of this research is to analyze the factors contributing to non-compliance among fathers with civil servant status, assess the implementation process of court decisions, evaluate the execution model employed by the PTA of Bengkulu, and explore avenues for its improvement. The study is grounded in the theories of the supremacy of law, law enforcement, and legal execution, employing a normative-empirical approach with descriptive methods. Data collection techniques included observation, interviews, and document analysis. The findings reveal that several factors, including economic constraints and limited legal awareness, contribute to the non-compliance of civil servant fathers in fulfilling child support obligations. The execution process is largely similar to the procedures for enforcing monetary payments. The PTA of Bengkulu has innovatively introduced the E-Mosi Caper application to monitor compliance and track the implementation of child support orders. To enhance the effectiveness of this execution model, the study proposes regulatory harmonization, the establishment of a dedicated implementation team, and heightened public awareness campaigns. These measures aim to support the development of a more robust and efficient system for ensuring compliance with child support obligations, ultimately advancing the protection of women’s and children’s financial rights after divorce. Penegakan hukum terhadap kewajiban nafkah anak oleh ayah berstatus Pegawai Negeri Sipil (PNS) pasca perceraian sering kali menghadapi kendala, seperti ketidakpatuhan dalam melaksanakan putusan Pengadilan Agama. Penelitian ini berfokus pada Pengadilan Tinggi Agama (PTA) Bengkulu, yang telah menerapkan sistem eksekusi untuk menjamin hak-hak finansial perempuan dan anak setelah perceraian. Tujuan utama dari penelitian ini adalah menganalisis faktor-faktor yang menyebabkan ketidakpatuhan ayah berstatus PNS, menilai proses pelaksanaan putusan pengadilan, mengevaluasi model eksekusi yang diterapkan oleh PTA Bengkulu, serta mengeksplorasi cara-cara untuk meningkatkan efektivitas sistem tersebut. Penelitian ini didasarkan pada teori supremasi hukum, penegakan hukum, dan eksekusi hukum, dengan pendekatan normatif-empiris menggunakan metode deskriptif. Teknik pengumpulan data meliputi observasi, wawancara, dan analisis dokumen. Hasil penelitian menunjukkan bahwa beberapa faktor, seperti keterbatasan ekonomi dan rendahnya kesadaran hukum, berkontribusi pada ketidakpatuhan ayah PNS dalam memenuhi kewajiban nafkah anak. Proses eksekusi menyerupai pelaksanaan pembayaran uang. PTA Bengkulu memanfaatkan aplikasi E-Mosi Caper untuk memantau kepatuhan dan melacak pelaksanaan perintah nafkah anak. Untuk meningkatkan efektivitas model eksekusi ini, penelitian ini mengusulkan harmonisasi regulasi, pembentukan tim pelaksana khusus, dan kampanye peningkatan kesadaran publik. Langkah-langkah ini bertujuan untuk mendukung pengembangan sistem yang lebih kuat dan efisien dalam menjamin kepatuhan terhadap kewajiban nafkah anak, sehingga pada akhirnya memperkuat perlindungan hak-hak finansial perempuan dan anak setelah perceraian.